2013
DOI: 10.1128/aem.02017-13
|View full text |Cite
|
Sign up to set email alerts
|

Streptomycin Application Has No Detectable Effect on Bacterial Community Structure in Apple Orchard Soil

Abstract: Streptomycin is commonly used to control fire blight disease on apple trees. Although the practice has incited controversy, little is known about its nontarget effects in the environment. We investigated the impact of aerial application of streptomycin on nontarget bacterial communities in soil beneath streptomycin-treated and untreated trees in a commercial apple orchard. Soil samples were collected in two consecutive years at 4 or 10 days before spraying streptomycin and 8 or 9 days after the final spray. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
2
29
0
1
Order By: Relevance
“…At present, it is difficult to ascertain whether antibiotics reaching the environment at low concentrations exert a substantial selective pressure on ARGs or ARB 50,51 . However, there is increasing evidence showing that repeated exposure of the environment to anthropogenically generated ARGs (for example, soil manure) correlate with the emergence and proliferation of ARGs in indigenous microbiota 66,67,73,74 . However, the impact of animal production on the propagation of antibiotic resistance is demonstrated by some zoonotic species of the genera Salmonella, Campylobacter, Listeria, Staphylococcus, Enterococcus and Escherichia, which are known to exhibit high levels of acquired antibiotic resistance 29,[75][76][77][78] .…”
Section: Critical Control Pointsmentioning
confidence: 99%
“…At present, it is difficult to ascertain whether antibiotics reaching the environment at low concentrations exert a substantial selective pressure on ARGs or ARB 50,51 . However, there is increasing evidence showing that repeated exposure of the environment to anthropogenically generated ARGs (for example, soil manure) correlate with the emergence and proliferation of ARGs in indigenous microbiota 66,67,73,74 . However, the impact of animal production on the propagation of antibiotic resistance is demonstrated by some zoonotic species of the genera Salmonella, Campylobacter, Listeria, Staphylococcus, Enterococcus and Escherichia, which are known to exhibit high levels of acquired antibiotic resistance 29,[75][76][77][78] .…”
Section: Critical Control Pointsmentioning
confidence: 99%
“…Sequencing offers distinct advantages such as the ability to evaluate species richness in much higher detail as even rare community members can be captured leading to a more unbiased evaluation of species richness (Bent and Forney, 2008). Although high-throughput sequencing of 16S rRNA genes is now a mainstream approach in microbial ecology research (Jansson, 2011), it has only recently been applied in ecotoxicological studies on bacterial communities (Table S1; Berg et al, 2012;Ge et al, 2012;Shade et al, 2013). However, estimates of species richness may still be biased and therefore unreliable (Gihring et al, 2012).…”
Section: Rrna and Functional Gene-based Community Analysismentioning
confidence: 99%
“…No overall effects on community diversity, evenness or structure were observed. However, rarer taxa belonging to Proteobacteria, Bacteroidetes and Actinobacteria, that were not observed in soil samples from under unsprayed trees, were detected in the post-spray samples with one, a Flavobacterium, consistently observed (Shade et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Islas-Espinoza et al (2012) observed an increase in species richness as determined by Shannon-Wiener and Margalef indexes in a soil supplemented with sulfamethazine. Shade et al (2013), using a 16S rRNA gene sequencing approach, compared soil bacterial communities under apple trees (Malus domestica) that had undergone spray treatments with streptomycin sulphate. No overall effects on community diversity, evenness or structure were observed.…”
Section: Introductionmentioning
confidence: 99%